Micromamíferos y metales pesados: biomonitorización del medio ambiente - Kolf-clauw, M.; Guénin, A.; Pérez López, M. (Observatorio Medioambiental, 2007)
Environmental biomonitoring constitutes one of the most important research lines recently developed in Ecotoxicology. This tool helps to evidence and characterize the effect of environmental contaminants on ecosystems, even before those environmental contaminants could be directly measured in the nature. At the present work, a review about recent research of adequate animal species which could be used to improve biomonitoring programs of heavy metal environmental contamination is shown.